A Rare Case of Bilobed Gallbladder with Two Cystic Ducts - Piyush Sharma; Ved Prakash; Bhanoo Chaudhary (Archives of Medicine and Health Sciences)
Bilobed or duplicate gallbladders are the rare anomalies of the biliary system occurring between the 5th and 6th weeks of embryonic life, of which Type 2 ductular variant is the commonest. Patients may be asymptomatic or symptomatic, with majority of the cases being detected intraoperatively or during re-operation. Once suspected a detailed preoperative evaluation is a must to avoid both intraoperative and postoperative complications. We report a case of a 34-year-old female who presented with acute onset of abdominal pain and was detected with symptomatic bilobed gallbladder (H Type) with cholelithiasis, with a resolution of symptoms after a successful laparoscopic cholecystectomy. The case emphasizes the importance of detailed preoperative evaluation in the form of ultrasound and magnetic resonance cholangiopancreatography to be considered during the management of biliary pathologies to avoid any intra- and post-operative complications.